2011
DOI: 10.1007/s10682-011-9465-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity of life history traits in relation to reproductive strategies in Boa constrictor occidentalis

Abstract: The close connection between reproductive ecology and life history in snakes leads to trade-offs between reproductive and other life-history traits. Optimal energy allocation to growth and reproduction is a key factor to determine life history structure. Therefore, elucidating the relationship between body size variations and reproductive characters is essential for a better understanding of life-history plasticity. The aim of this work was to determine to what extent life-history differs among populations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…3). Distribution of Squamata fauna in South America is generally closely related to vegetation features (Nogueira et al, 2009) because vegetation might regulate ecological processes (Cardozo et al, 2007;Cardozo and Chiaraviglio, 2011). For instance, Cardozo et al (2007) demonstrated that dispersal of ectotherms is influenced hy vegetation loss, and showed phenotypic plasticity in lifehistory traits in relation to landscape vegetation changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Distribution of Squamata fauna in South America is generally closely related to vegetation features (Nogueira et al, 2009) because vegetation might regulate ecological processes (Cardozo et al, 2007;Cardozo and Chiaraviglio, 2011). For instance, Cardozo et al (2007) demonstrated that dispersal of ectotherms is influenced hy vegetation loss, and showed phenotypic plasticity in lifehistory traits in relation to landscape vegetation changes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, environmental temperature might influence diverse behavioural responses (Gifford et al, 2008;Cury de Barros et al, 2010) and trigger reproductive activity in teiid lizards from temperate zones (Cruz et al, 1999). In addition, the spatial pattern of vegetation cover affects thermoregulatory processes in ectotherms (Chiaraviglio, 2006;Cardozo and Chiaraviglio, 2011). Accordingly, Chiarello et al (2010) hypothesized that vegetation pattern might influence basking of active heliothermic lizards like Tupinambis.…”
Section: Introductionmentioning
confidence: 99%
“…Their occurrence in still remote areas (Beni river valley in Bolivia and Marajó region in northern Brazil, respectively; 48, 49) certainly accounts for the lack of videos depicting these two species. Since the largest animals are more likely to be killed – which in large constrictors are the females with highest reproductive output [38,39,60,61] – this could generate a conservation problem for these two smaller-ranged anaconda species.…”
Section: Implications For Conservationmentioning
confidence: 99%
“…Among the environmental factors that might influence behaviors in Squamata, vegetation structure would be of great importance (Blouin-Demers & Weatherhead, 2001;Chiaraviglio & Bertona, 2007;Row & Blouin-Demers, 2006) because it provides alternative thermal environments for thermoregulation (Chiaraviglio, 2006) and might affect reproductive processes and life history traits (Cardozo & Chiaraviglio, 2008;Cardozo & Chiaraviglio, 2011). Therefore, according to the complexity of the vertical structure of the land covers, we determined three major vegetation classes: forest, shrublands and low vertical structures (LVS).…”
Section: Landscape Analysismentioning
confidence: 99%